Extracellular Alpha-Synuclein Oligomers Modulate Synaptic Transmission and Impair LTP Via NMDA-Receptor Activation - Diógenes, Maria José (2013)
Parkinson’s disease (PD) is the most common representative of a group of disorders known as synucleinopathies, in which misfolding and aggregation of -synuclein (a-syn) in various brain regions is themajorpathological hallmark. Indeed, themotorsymptomsinPDare causedby a heterogeneous degeneration of brain neurons not only in substantia nigra pars compacta but also in other extrastriatal areas of the brain. In addition to the well known motor dysfunction in PD patients, cognitive deficits and memory impairment are also an important part of the disorder, probably due to disruption of synaptic transmission and plasticity in extrastriatal areas, including the hippocampus. Here, we investigated the impact of a-syn aggregation onAMPAandNMDAreceptor-mediated rat hippocampal (CA3-CA1) synaptic transmission and long-term potentiation (LTP), the neurophysiological basis for learning and memory. Our data show that prolonged exposure to a-syn oligomers, but not monomers or fibrils, increases basal synaptic transmission through NMDA receptor activation, triggering enhanced contribution of calcium-permeable AMPA receptors. Slices treated with a-syn oligomers were unable to respond with further potentiation to theta-burst stimulation, leading to impaired LTP. Prior delivery of a low-frequency train reinstated the ability to express LTP, implying that exposuretoa-synoligomersdrivestheincreaseofglutamatergicsynaptictransmission,preventingfurtherpotentiationbyphysiologicalstimuli. Our novel findings provide mechanistic insight on how a-syn oligomers may trigger neuronal dysfunction and toxicity in PD and other synucleinopathies.